From rogue sign to squatter symbol: Origins of an urban meme - Wasielewski, Amanda (City (London, England), 2019)
The international symbol for squatting originated in Amsterdam in late 1979. Its origins and particular meaning are less clear. This article investigates several possible influences on the design of the symbol and its significance as an urban meme.